Cover Feature: Magnetic Slow Relaxation in a Metal–Organic Framework Made of Chains of Ferromagnetically Coupled Single‐Molecule Magnets (Chem. Eur. J. 27/2018). Issue 27 (16th April 2018) - Huang, Gang; Fernandez‐Garcia, Guglielmo; Badiane, Insa; Camarra, Magatte; Freslon, Stéphane; Guillou, Olivier; Daiguebonne, Carole; Totti, Federico; Cador, Olivier; Guizouarn, Thierry; Le Guennic, Boris; Bernot, Kevin
Abstract : Ferromagnetic interactions induced by metal—organic framework (MOF) architecture turn a poor single‐molecule magnet (SMM) into a slow relaxing material. The MOF is made of nine‐coordinated Dy III magnetic building blocks (MBBs) with poor intrinsic SMM behavior. However, the MOF architecture constrains the MBBs in a one‐dimensional structure that induces a ferromagnetic coupling between them. More information can be found in the Full Paper by B. Le Guennic, K. Bernot et al. onpage 6983 .